From ink to byte - Codevilla, Fernanda (2023)
The interview with Dr. Cristiana Barreto, who was one of the editors of Revista da SAB in the 2014-2015 biennium, recalls a fundamental moment in the history of the journal: the transition from the traditional print format to the digital format and the beginning of editorial management through a free access platform . In the interview, Cristiana Barreto also reflects on some of the magazine's current and future challenges.